Rheumatic Manifestations and Diseases From Immune Checkpoint Inhibitors in Cancer Immunotherapy - Shen, Pan; Deng, Xuan; Hu, Zhishuo; Chen, Zhe; Huang, Yao; Wang, Ke; Qin, Kai; Huang, Ying; Ba, Xin; Yan, Jiahui; Han, Liang; Tu, Shenghao (Frontiers in Medicine, 2021)
Immune checkpoint inhibitors (ICIs), which can enhance antitumor immunity and inhibit cancer growth, have revolutionized the treatment of multiple cancers and dramatically decreased mortality. However, treatment with ICIs is directly associated with immune-related adverse events (irAEs) because of inflammation in off-target organs and autoimmunity resulting from non-specific immune activation. These irAEs can cause rheumatic diseases and manifestations such as inflammatory arthritis, polymyalgia rheumatica, myositis, vasculitis, Sicca and Sjogen's syndrome, and systemic lupus erythematosus. Early diagnosis and treatment of these adverse events will improve outcomes and quality of life for cancer patients. The treatment of rheumatic diseases induced by ICIs requires multidisciplinary cooperation among physicians. Furthermore, the underlying mechanisms are not fully understood and it is difficult to predict and evaluate these side effects precisely. In this review, we summarize available studies and findings about rheumatic irAEs, focusing mainly on the clinical manifestations, epidemiology, possible mechanisms, and guiding principles for treating these irAEs.